Trust frameworks and technology: water quality engagement with Australian farming stakeholders - Aaron M. Davis; Anthony J. Webster; Simon Fielke; Luke Buono; Sheriden Morris; Rickard Abom (Frontiers in Sustainable Food Systems)
This paper provides a community case study of the ongoing process of farming stakeholder engagement in a high priority Great Barrier Reef catchment that emphasizes stakeholder co-design and use of sensor technologies in water quality engagement and communication. Provision of near real-time visual evidence of the ‘data’ (e.g., nitrate-nitrogen readings, rainfall data and river heights at local scales) helped break down historic communication barriers and led to the articulation of farmer trust and confidence in the water quality science as partners in the scientific process. This confidence in interpretation of ‘trustworthy’ scientific information created the opportunity for growers to share and discuss experiences with neighbors, enabled peer-to-peer leadership, and facilitated on-farm practice changes and experiments. Social research highlighted the importance of investing in building a trust-based environment for dialogue between growers and scientists on a contentious topic, with farming stakeholders reporting improved communication, an improved trust environment with more direct oversight of monitoring data, and ‘space’ to learn and experiment as contributing factors to their engagement. The Project 25 framework is now being held up as an industry model for stakeholder engagement, and industry support is emerging for similar programs in neighboring catchments.